(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
This study investigates the traditional food environment, consumption patterns, nutritional values, and the factors influencing the intake of indigenous foods (IFs) among the Munda tribal community in Ranchi district, Jharkhand, India. Utilizing a cross-sectional mixed-method approach, the research delves into the diverse types of food environments (wild, cultivated, and built) that the Munda people interact with, alongside the nutritional properties of the IFs they consume. Findings indicate a rich traditional ecological knowledge (TEK) surrounding IFs, although a significant portion remains underutilized due to socio-cultural and environmental challenges. The study highlights the importance of preserving traditional food systems and integrating formal and informal food literacy to enhance the nutritional well-being of the Munda community, amidst the challenges posed by climate change and modern agricultural practices.